1999
DOI: 10.1128/mcb.19.7.5073
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Withdrawal Promotes Myogenic Induction of Akt, a Positive Modulator of Myocyte Survival

Abstract: During myogenesis, proliferating myoblasts withdraw from the cell cycle, acquire an apoptosis-resistant phenotype, and differentiate into myotubes. Previous studies indicate that myogenic induction of the cyclindependent kinase inhibitor p21 results in an inhibition of apoptotic cell death in addition to its role as a negative cell cycle regulator. Here we demonstrate that the protein encoded by the Akt proto-oncogene is induced in C2C12 cells during myogenic differentiation with a corresponding increase in ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
199
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(214 citation statements)
references
References 58 publications
13
199
2
Order By: Relevance
“…39 Since signaling through the PI3-kinase pathway has been shown to be critical for normal skeletal myoblast survival/differentiation, 20,21,23,24 and Ras signaling abrogates differentiation, 29,30,37,38 we focused our attention on the Raf/MEK pathway which has been shown to be anti-apoptotic. 33 We have shown that signaling through MEK may play a role in the survival of myoblasts in GM since the abrogation of MEK signaling increases apoptosis in GM to almost the level observed when myoblasts are cultured in DM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39 Since signaling through the PI3-kinase pathway has been shown to be critical for normal skeletal myoblast survival/differentiation, 20,21,23,24 and Ras signaling abrogates differentiation, 29,30,37,38 we focused our attention on the Raf/MEK pathway which has been shown to be anti-apoptotic. 33 We have shown that signaling through MEK may play a role in the survival of myoblasts in GM since the abrogation of MEK signaling increases apoptosis in GM to almost the level observed when myoblasts are cultured in DM.…”
Section: Discussionmentioning
confidence: 99%
“…Myoblasts expressing constitutively active Ras (A2:H-Ras myoblasts) are differentiation-defective 29,30 ( Figure 4A) and apoptose at a level less than 1/10 that of the parental 23A2 myoblasts in either GM ( Figure 4B Signaling by Ras through either the PI3-kinase/Akt pathway 32 or the Raf/MEK/MAPK pathway has been implicated in cell survival. 33 Since PI3 kinase/Akt signaling has been implicated in the normal survival/differentiation of skeletal myoblasts, 20,21,23,24 we focused on the role of Raf/ MEK signaling in the increased survival of A2:H-Ras myoblasts. We have previously reported that PD 098059, a selective MEK inhibitor, does not affect the differentiation of skeletal myoblasts.…”
Section: Abrogation Of Differentiation Can Be Separated From Abrogatimentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, wortmannin (100 and 500 nM) and LY (10 mM) had no significant effect on the control cells (data not shown), while LY (20 mM) increased apoptosis of the control cells to about 72% after UVA exposure. When ULTH cells were infected with dominant-negative AKT (DN-AKT) (Fujio et al, 1999) or wild-type PTEN (Huang and Kontos, 2002) adenovirus vectors, more ULTH cells underwent apoptosis upon UVA exposure than did cells infected with the empty vector (EV) (Figure 7d and e). In contrast, no significant effect was observed with the control cells under the similar conditions (data not shown).…”
Section: Ulth Cells Acquired Generalized Resistance To Apoptogenic Agmentioning
confidence: 99%
“…Hypophosphorylated retinoblastoma protein is also required for protection against apoptosis (Wang et al, 1997). Akt, a proto-oncogene product, functions downstream of p21 in promoting myocyte survival (Fujio et al, 1999).…”
Section: Coordinate Regulation Of Cell Cycle Withdrawal and Apoptosismentioning
confidence: 99%